INTENSITAS SYARIAH DALAM NEGARA BERDASAR ATAS KETUHANAN YANG MAHA ESA - Arlis Arlis (Institut Agama Islam Negeri Batusangkar, 2017)
Sharia is the law of God. The intensity of the Shari'ah refers to the conditio sin qua non for the good sake of mankind. Moreover, the state principles of Indonesia clearly mentions that this country believes in God the Almighty. However, the facts show that the Shari'ah has not become the soul of way of life of the nation. In fact, the concept of Shariah itself in some contemporary Islamic discussions is debatable due to its narrow and improper definition. Consequently debates concerning with the implementation leads serious problems. This article aims at elaborating the concept of Sharia intensity, existence, and its implementation in a state that bases its believe in God the Almighty through philosophical, legal and sociological approaches.